Judgment before Nuremberg : the Holocaust in the Ukraine and the first Nazi war crimes trial - Dawson, Greg (Pegasus books, 2012)
When we reflect on the Holocaust, we think of Auschwitz and Dachau; and when we think of justice for this terrible chapter in history, we think of Nuremberg. Not Russia or the Ukraine, and certainly not the town of Kharkov (Kharkiv in Ukrainian). But in reality, the first war-crimes trial against the Nazis was in this Ukrainian city, where in a sense the Holocaust itself began. Eighteen months before the end of World War II, three Nazi officers and a Ukrainian collaborator were tried and convicted of war crimes in a Soviet court and hanged in Kharkov's public square. Revealing a lost chapter in Holocaust historiography, journalist Greg Dawson tells of his journey to this place, and the rediscovery of the forgotten trial which began the process of avenging the murder of his grandparents, great-grandparents, and tens of thousands of fellow Ukrainians consumed at the dawn of the Shoah.--From publisher description